Avaliação do uso de lodo do tratamento físico-químico como auxiliar de coagulação para tratamento de água residuária de cervejaria - Machado, Alfredo Rodrigo Lins (2022)
This work aimed to analyze the physical-chemical treatment of wastewater from a brewery located in the city of Londrina - PR, using the sludge generated in the treatment as a coagulation aid. In the present study, the analyzes were divided into 4 groups and within each group varying pH and aluminum sulfate concentration. The first treatment was performed using only the aluminum sulfate coagulant for the treatment. In the second group, the sludge generated in the first treatment combined with aluminum sulfate was used. Then, after treatment, the values obtained in each of the two groups were compared. The third treatment group, like the first, was performed using only the aluminum sulfate coagulant. In the fourth and last group, the sludge generated in the previous treatment was used, but before using it in the treatment, the sludge was acidified and then combined with aluminum sulfate for the treatment. After the two treatments, the results obtained were compared. The best turbidity removal values for each of the four groups were 95.06% removal with pH 7 and concentration 100 mg/L for group 1, with pH 5 and concentration 50 mg/L + sludge - 86.71 % removal for group 2, with pH 5 and concentration 100 mg/L - 97.31% removal for group 3 and finally pH 7 and concentration 50 mg/L + acidified sludge - 94.46% removal for group 4. The generation of sludge obtained values between 0 mL/L (pH 7 and pH 9 with concentrations of 60 mg/L of sulfate) to 165 mL/L (pH 7 with concentration of 50 mg/L combined with LA). As for residual aluminum, the values obtained were in the order of 1.87% to 7.17% when analyzing the treatments made using only aluminum sulfate (groups 1 and 3).